Rimklb mutation causes male infertility in mice - Koji Maekura; Satoshi Tsukamoto; Michiko Hamada-Kanazawa; Masaoki Takano (Scientific Reports, 2021)
Abstract Rimklb is a mammalian homologue of the E. coli enzyme RimK, which catalyzes addition of glutamic acid to the ribosomal protein S6. To date, no previous studies have shown any physiological role for Rimklb in mammals. In this study, using Western blotting, we found that Rimklb is distributed and expressed in mouse testis and heart. Rimklb was subsequently localized to the testicular Leydig cells using immunohistochemistry with an anti-Rimklb antibody. We generated a Rimklb mutant mouse in which a three-base deletion results in deletion of Ala 29 and substitution of Leu 30 with Val, which we named the RimklbA29del, L30V mutant mouse. RimklbA29del, L30V mutant mice show a decrease in testicular size and weight, and in vitro fertilization demonstrates complete male infertility. Furthermore, we found that a key factor in the mammalian target of the rapamycin/ribosomal protein S6 transcriptional pathway is hyperphosphorylated in the seminiferous tubules of the mutant testis. We conclude that Rimklb has important roles that include spermatogenesis in seminiferous tubules. In summary, male RimklbA29del, L30V mice are infertile.